Swimming Australia - Annual Report 2007-08 (2007)
Australia, for its small population and remote location, continues to confound the world with its achievements on the international sporting stage. This has been achieved through the development of a comprehensive and effective national sports system that encourages sport and physical activity for all Australians and creates opportunities to enable those who are talented and motivated to reach their potential. This system has evolved with the strong support of the Australian Government, state, territory and local governments, the private sector and sporting organisations at all levels. In 2007-08, the Australian Government, through the Australian Sports Commission, provided Swimming Australia with funding of over $6.2 million for the development of the sport and its continued enhancement at the grassroots and elite levels, including $1.5 million support for the Swimming program at the Australian Institute of Sport, with a further $541,000 going directly to swimmers under the Australian Government Sport Training Grant scheme. Advances in sports science included establishing an integrated performance analysis system for the Olympic trials, allowing all state institutes and academies of sport to access video footage and analyse performances immediately after races. This system provided coaches with real-time analysis of their athletes` performances, which is a significant advancement on previous technology. The High Performance unit also further refined the funding model to the state institutes and academies of sport and established the central management of the sports science and sports medicine network.